Green Business Strategy For The Processed Seaweed MSMEs (Case Study At Tarakan City Coastal) - Sulistya Rini Pratiwi (Publikasi Indonesia, 2022)
The issue of green business is a small part of a big issue that actually has hit the headlines of economic growth in the future, namely the sustainability of the business. The MSME (Micro, Small and Medium Enterprises) sector has an important role to make it happen. The development of MSMEs is one of the efforts in the development of potential coastal communities. Micro Small and Medium Enterprises (MSMEs) activities have an important role in realizing the sustainability business issue. The object of this research is to analyze strategic planning in developing sustainable MSMEs through financial analysis and SWOT analysis. The feasibility analysis analyzed using cost-benefit analysis (CBA). CBA consist of Net Present Value (NPV), Internal Rate Return (IRR) and Benefit Cost Ratio (BCR). The results show that this business is feasible and profitable, NPV is Idr.133,813,050, IRR value equal to 2.417, or bigger than prevailing bank interest is 13%, Net B/C Ratio of 3.29, BEP of 38 packs per month and PBP of 4 months. The right development strategy used by processing seaweed MSMEs is a rapid strategy by utilizing the existing strengths and opportunities. Strategies that can be done is increasing cooperation between business actors and product diversification.